Pengaruh Jenis dan Dosis Pupuk Kandang terhadap Pertumbuhan dan Hasil Tanaman Kacang Panjang (Vigna Sinensis L.) - Deajeng Putri Safira Nariswari; Ramdan Hidayat; Felicitas Deru Dewanti (BPFP Universitas Bengkulu, 2024)
THE EFFECT OF TYPE AND DOSAGE OF MANURE ON THE GROWTH AND YIELD OF YARDLONG BEAN PLANTS (Vigna sinensis L.)]. The growth and yield of yardlong bean plants are significantly influenced by the type and dosage of fertilizer applied. Manure is one of the organic fertilizer options that can enhance soil fertility and plant productivity. This study aims to determine the optimal type and dosage of manure for the growth and yield of yardlong bean plants. The research was conducted from May to July 2023 on dry land in Tulungrejo Village, Karangrejo District, Tulungagung Regency, East Java Province, located between 7° 51' to 8° 81' S and 111° 43' to 112° 07' E, with air temperatures ranging from 24 °C to 30 °C. The research method used was a factorial experiment with a completely randomized design (CRD), consisting of two factors: type of manure (cow, goat, and chicken) and dosage of manure (10, 20, 30, and 40 tons per hectare). The results showed that the combination of type and dosage of manure had a significant effect on the average pod length, total pod weight per plant, and plant height at 29 and 36 days after planting (DAP). Cow manure at a dosage of 20 tons/ha resulted in the best growth and yield of yardlong bean plants compared to other treatment combinations. The implications of this research indicate that the use of cow manure at the appropriate dosage can enhance the efficiency of growth and yield in yardlong bean plants. This provides guidance for the community in selecting the optimal type and dosage of manure to achieve maximum productivity.